2004
DOI: 10.1002/sia.1679
|View full text |Cite
|
Sign up to set email alerts
|

Methodical aspects in the surface analysis of supported molybdena catalysts

Abstract: Supported molybdena catalysts, with TiO 2 , CeO 2 and Al 2 O 3 supports, were studied by XPS and ISS. It was found that reliable results are obtained only when samples are calcined and transferred into the ultrahigh vacuum system without further contact with the ambient atmosphere ('in situ calcination'). This applies also to catalysts that were previously calcined but had been stored in the ambient atmosphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…This was again shown in a series of systematic studies of supported metal oxide catalysts [75][76][77]. This was again shown in a series of systematic studies of supported metal oxide catalysts [75][76][77].…”
Section: Low-energy Ionssupporting
confidence: 57%
“…This was again shown in a series of systematic studies of supported metal oxide catalysts [75][76][77]. This was again shown in a series of systematic studies of supported metal oxide catalysts [75][76][77].…”
Section: Low-energy Ionssupporting
confidence: 57%
“…Note that for theoretical reasons each 3d 5/2 -3d 3/2 doublet has a fixed intensity ratio and a fixed energy separation. In a recent paper, Briand et al [41] reported on the methodical aspects in the XPS analysis of molybdena catalysts with TiO 2 , CeO 2 and Al 2 O 3 supports. Hercules and coworkers also found that the catalytic activity for propene hydrogenation and for propane hydrogenolysis increases for Mo oxidation states ≤ +4.…”
Section: Thermochemical Approachmentioning
confidence: 99%
“…[12,14,15] In methanol oxidation studies, similar catalytic turnover frequencies were found over bulk mixed-metal oxides and related supported metal oxides (e.g., Fe 2 (MoO 4 ) 3 and MoO 3 /Fe 2 O 3 ), which supports the idea of surface MoO x enrichment of the bulk phases. [16][17][18][19] These observations, however, are qualitative as exposed metal oxide ions of low catalytic activity would not be detected by the test reaction. Thus, we have undertaken a study of the outermost surface compositions of such compounds by LEIS and excitation-energy resolved XPS (ERXPS).…”
mentioning
confidence: 92%